Formulation Development and In vitro Evaluation of Combination Product of Glyburide and Metformin Hydrochloride Tablet - Chowdhury, Mohammed Motaher Hossain; Nawreen, Abedah; Rana, Md Sohel (Bangladesh Pharmaceutical Journal, 2015)
This study was attempted to formulate a combination product of Glyburide and Metformin Hydrochloride Tablets USP 2.5mg/500mg and to evaluate their physico-chemical properties. Wet granulation method was adopted for preparation of tablet using different excipients namely Microcrystalline cellulose, Povidone K-30, Copovidone, Croscarmellose sodium and Sodium stearyl fumerate in six different formulations (F1-F-6). The granules for tabletting were evaluated for angle of repose, bulk density, tapped density, compressibility index and drug content etc. The tablets were subjected to thickness, hardness, friability, disintegration and in vitro release studies. The results of physical parameters of tablets showed that there were capping, hardness and friability problems in formulation F-1, F-2 and F-3. Granules of formula F-4, F-5 and F-6 showed satisfactory flow properties, compressibility index and the physical parameters of tablets from these three formulations gave optimum result in comparison to innovator's brand. Disintegration time of these three formulations (7-8 min) was found similar with innovator's brand (6.30-7.30 min). Assay of formula F-6 of glyburide (97.97%) and Metformin Hydrochloride (100.2%) met the USP specification (90%-110%). It was also found that dissolution profile of Glyburide depends on particle size of Glyburide powder. When micronized and non micronized grade of Glyburide was used in a ratio of 3:1 (F-6) it gave similar dissolution profile as innovator's brand where the similarity factor (f2) was calculated as 59. On the other hand, dissolution profile of Metformin hydrochloride was found similar in all the three formulations (F-4, F-5, F-6) with reference to innovator having all f2 values above 50. Formulation F-6 possessed good stability in accelerated condition for 6 months study. By comparing the dissolution profiles with the innovator's drug glucovance® tablet, it was revealed that the formulation F-6 exhibit similar drug release profile for both Glyburide and Metformin Hydrochloride. DOI: http://dx.doi.org/10.3329/bpj.v16i2.22304 Bangladesh Pharmaceutical Journal 16(2): 195-203, 2013